Biomechanics of the bobsleigh push phase - Zedler, M.; Braunstein, B.; Potthast, W.; Goldmann, J.-P. (Journal of Sports Sciences, 2025)
The purpose of this work was to provide a fundamental, in-depth analysis of kinematics and kinetics of the bobsleigh push phase to establish a basis for performance analysis and enhancement. Fifteen elite male athletes performed maximal effort push starts, while ground reaction forces (GRF) and 3D marker trajectories were simultaneously recorded for ground contacts of different sub-sections of the push phase (start acceleration phase: first and second ground contact after the initial push-off from the start block, acceleration phase: 10 m and high-velocity phase: 30 m). To obtain a comprehensive view of the push phase, whole-body kinematics as well as joint kinetics were analysed and compared across the push phase. The results showed that propulsion during the start acceleration was hip extensor dominant. With increasing running speed, the contribution to propulsion increased at the ankle and decreased at the knee. In contrast to unresisted sprinting, bobsleigh athletes relied more on mechanical energy generation at the hip than at the ankle, especially during start acceleration. These findings should be considered for the strength and conditioning of bobsleigh athletes and further investigated in relation to a suitable performance measure.